People Smuggling in Indonesia - Zulyadi, Rizkan; Subramaniam, Geetha; Kamello, Tan (International Journal of Asian Social Science, 2014)
This article investigates the practice of people smuggling in Indonesia. Located in the center of international traffic, Indonesia has become a strategic place for this business. Besides, the absence of laws regulating this smuggling activity as well as the lack of coordination among institutions of the government has been a huge obstacle for resolving this problem. People smuggling may occur due to many factors, one of which is the encouraging factors that cause the immigrants to leave their country. Several actions that have been taken were merely based on the Immigration Law and the punishments were only given to the wrongdoers, while those asking to be smuggled escaped the law.